Overcoming barriers to orthodontic treatment in the United States - Triny Gutierrez (Wolters Kluwer Medknow Publications, 2016)
Underserved patients are at the highest risk for oral and overall health complications due to the many obstacles that prevent the group from receiving the most basic forms of health care. Receiving orthodontic care is even scarcer since most dental insurances regard it as an elective treatment, and only a limited number of orthodontists will treat these patients. The situation only worsens, as it appears that orthodontists in training intend to see even less of these patients in the future. Considerable changes need to be made. One change that needs to occur is within the dental training and education orthodontists receive. There needs to be a transition that encourages and promotes the development of skills necessary for treating underserved patients. Another change needs to occur in the restrictions that prevent specialists from participating in programs designed to provide relief in underserved areas. The events that would follow this change demonstrate the necessity for revisions in prohibitive policies against specialists. Finally, an initiative is needed to decrease costs associated with orthodontic treatment to make treatment more accessible, especially for patients with U.S. federally funded healthcare - Medicaid. Encouraging limited orthodontic treatment in mixed dentition (Phase I treatment) could aid in resolving this issue. The worsening situation among the underserved is connected to an unsustainable status quo. These issues need to be addressed and resolved to prevent any further onset and begin recovery.